Proposed Quality Improvement of Clutch Disc Products Using Statistical Quality Control and Fault Tree Analysis Methods at PT. Exedy Manufacturing Indonesia - Argaditia Mawadati (Universitas Pancasakti Tegal, 2022)
Exedy Manufacturing Indonesia is an automotive industry company that produces Clutch Assy Wheel 4 – Wheel 2 Clutch / Clutch, E. Spring, RLS Plate Motorcycle. Their average production capacity is 1,103 units of clutch discs per day. The company has a product defect standard that cannot exceed 3%, but currently, the average rate of product defects reaches 10%. There are three highest numbers of defective products, consisting of 609 units of consumable blades, 533 units of small size, and 571 units of uneven surface. This means that the quality control carried out by the company is still not optimal and needs improvement. This study aims to determine the number and the causes of defects and quality improvement using statistical quality control (SQC) and fault tree analysis (FTA) methods. From the SQC, it shows that 4 data exceed the upper control limit thus improvements need to be made. The results of the FTA method showed there are 10 basic events in determining the cut set, namely poor material quality, lack of experience, poor work procedures, fatigue, lack of skill, haste, air temperature, poor lighting, untidy area, and shrinking machine performance. Then a proposal for improvement is made to improve the factors that influence the cause of the defect.Keywords: Fault Tree Analysis, Quality Improvement, Statistical Quality Control